Metallic stents are more efficacious than plastic stents in unresectable malignant hilar biliary strictures: a randomized controlled trial. Issue 2 (February 2013) - Mukai, Tsuyoshi; Yasuda, Ichiro; Nakashima, Masanori; Doi, Shinpei; Iwashita, Takuji; Iwata, Keisuke; Kato, Tomohiro; Tomita, Eiichi; Moriwaki, Hisataka
Abstract Background Endoscopic biliary stenting is a well‐established palliative treatment for unresectable malignant biliary strictures, for which plastic tube stents (PSs) and self‐expandable metallic stents (SEMSs) are most commonly used. The efficacy of these stents has been extensively described in distal biliary strictures, but not in hilar biliary strictures. The present study aimed to compare the efficacy of PSs and SEMSs for unresectable malignant hilar biliary strictures. Methods From June 2004 to November 2008, 60 patients were enrolled and prospectively randomized into the PS or SEMS group. Results The 6‐month patency rate was significantly higher in the SEMS group than in the PS group (81 vs. 20%;p = 0.0012). Kaplan—Meier analysis showed significantly longer patency in the SEMS group than in the PS group (p = 0.0002); the 50% patency period was 359 days in the SEMS group and 112 days in the PS group. There was no significant difference in the overall survival period between the PS and SEMS groups (p = 0.2834). The mean number of reinterventions for stent failures was significantly lower in the SEMS group (0.63 times/patient) than in the PS group (1.80 times/patient) (p = 0.0008). The overall total cost for the treatment was significantly lower in the SEMS group than in the PS group (p = 0.0222). Conclusions SEMSs were associated with a longer patency than PSs in patients with unresectable hilar biliary stricture. SEMSs were also more advantageous in reducing the number of reintervention sessions and the overall treatment cost.